Developing TPACK based Assessment Instrument for Teaching Practice of English Education Students - Hamid, Syifa Fadhilah; Shopia, Khilda; Isnaniah, Isnaniah (JELLT (Journal of English Language and Language Teaching), 2024)
This study aimed to develop and validate a TPACK-based assessment instrument for English Education students during their teaching practice. Utilizing the Technology, Pedagogy, and Content Knowledge (TPACK) framework, this instrument evaluates pre-service teachers' competency in integrating technology into their instructional practices. A mixed-methods approach was employed, with qualitative data informing item development and quantitative methods used for validation. The instrument was refined through expert interviews, literature analysis, and cognitive interviews with target users, resulting in a 34-item survey covering seven TPACK-related factors: Technological Knowledge (TK), Content Knowledge (CK), Pedagogical Knowledge (PK), Pedagogical Content Knowledge (PCK), Technological Content Knowledge (TCK), Technological Pedagogical Knowledge (TPK), and Technological Pedagogical Content Knowledge (TPACK). The final assessment tool is organized into five components: Teaching Ability, Lesson Planning, Social Competence, Personality Competency, and Implementation Report. Each component integrates various TPACK constructs, ensuring a comprehensive evaluation of pre-service teachers' skills. This instrument is essential for enhancing TPACK proficiency in teacher education programs, aligning with educational standards and supporting the development of globally competitive teachers. Future research should explore the long-term impacts of TPACK proficiency on teaching effectiveness and student outcomes, further validating the framework's significance in modern education.